BENTUK KESEJAJARAN ANTARA REALITAS ‘AZRĀ’ JĀKARTĀ DAN REALITAS SEJARAH INDONESIA - Taufiq Ahmad Dardiri (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
The novel ‘Azrā`Jākartā, written by Najīb al-Kīlāniy, has its setting in Indonesia. The characters and the events of the novel are seen in its correspondence to the history of Indonesia in the 1960’s in many aspects. Those aspects are: 1) the presence of the communist ideology in Indonesia, 2) the Coupe d’tat or the sudden overthrow of a government by a usually small group of persons —Comunist Party, which was previously in positions of authority, thirdly is that the Moslem as the victims of this clash of ideology. From this study, it can be clearly seen that the historical events of the novel is the part of its structure. Furthermore, it’s not merely coincidently taken for granted; instead it has its meaning.